Cetacean sightings and acoustic detections in the offshore waters of the Maldives during the northeast monsoon seasons of 2003 and 2004 - Clark, Rebecca A.; Johnson, Christopher M.; Johnson, Genevieve; Payne, Roger; Kerr, Iain; Andersen, R. Charles; Sattar, Shahaama A.; Godard, Celine A. J.; Madsen, Peter T. (J. Cetacean Res. Manage., 2023)
Despite its central position in the Indian Ocean Sanctuary, little is known about the offshore cetacean fauna of the Maldives. Here we report survey results gathered by the R/V Odyssey in the Maldives during the 2003 and 2004 northeast monsoon seasons, and provide data on cetaceans from visual and acoustic observations. The survey was conducted over a period of 72 days and covered 10,915 track line kilometres. The main aim of the survey was to collect biopsy samples from sperm whales (Physeter macrocephalus) as part of a global survey of ocean pollutants. Totals of 157 sightings and 1,461 acoustic detections of 16 identified cetacean species were recorded. Risso’s dolphin (Grampus griseus), pantropical spotted dolphin (Stenella attenuata), spinner dolphin (Stenella longirostris) and sperm whale were the most commonly sighted species. Sperm whales and pantropical spotted dolphins were particularly abundant in the southern Maldives. The cetacean acoustic detection rate was 2.5 times higher than in the eastern Indian Ocean and Western tropical Pacific, while the non-physeterid sighting rate was 1.7 times higher than the Eastern tropical Pacific and 6.7 times higher than the eastern Indian Ocean based on other research conducted by the R/V Odyssey using the same methodology. It is concluded that the Maldives has a diverse and seemingly abundant cetacean community.